Continuing project to synthesize information on highway problems. (Research results digest (National Cooperative Highway Research Program), 1983)
"A staff digest of the progress and status of NCHRP Project 20-5, "Synthesis of information related to highway problems," for which the Transportation Research Board is the agency conducting the research."